2023
DOI: 10.7759/cureus.36184
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Synthase Inhibitors and Dietary Interventions: A Combined Novel Approach for Prevention and Treatment of Cardiovascular Disease

Abstract: Systemic hypertension (HTN) is the hallmark of cardiovascular disease and the forerunner of heart failure. These associations have been established over decades of research on essential HTN. Advancements in the treatment of patients diagnosed with HTN, consisting of alpha-or beta-adrenergic receptor blockers, calcium channel blockers, angiotensin-converting enzyme inhibitors, thiazide, or aldosterone receptor blockers known as anti-mineralocorticoids, in the presence or absence of low sodium salt diets, often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…At variance with MRAs which target to mitigate the effects of aldosterone, Asis act one step earlier by inhibiting the production of aldosterone itself [59]. Baxdrostat is a highly selective Asi, with no impact on cortisol secretion, that has shown promising results in the treatment of resistant hypertension [60]. In a recently published phase 2 trial (BrigHTN), baxdrostat exhibited a dose-dependent reduction in systolic blood pressure when compared with placebo (2 mg vs. placebo: −11.0 mmHg [95%CI −16.4 to −5.5; p < 0.001]; 1 mg vs. placebo: −8.1 mmHg [95%CI, −13.5 to −2.8; p = 0.003]) [43].…”
Section: Aldosterone Synthase Inhibitorsmentioning
confidence: 99%
“…At variance with MRAs which target to mitigate the effects of aldosterone, Asis act one step earlier by inhibiting the production of aldosterone itself [59]. Baxdrostat is a highly selective Asi, with no impact on cortisol secretion, that has shown promising results in the treatment of resistant hypertension [60]. In a recently published phase 2 trial (BrigHTN), baxdrostat exhibited a dose-dependent reduction in systolic blood pressure when compared with placebo (2 mg vs. placebo: −11.0 mmHg [95%CI −16.4 to −5.5; p < 0.001]; 1 mg vs. placebo: −8.1 mmHg [95%CI, −13.5 to −2.8; p = 0.003]) [43].…”
Section: Aldosterone Synthase Inhibitorsmentioning
confidence: 99%
“…5 Clinical research has demonstrated that aldosterone synthesis inhibitors lower circulating aldosterone levels by directly blocking the synthesis of aldosterone rather than blocking its receptor activity, subsequently lowering BP. 6 The first aldosterone synthase inhibitor to be developed was Osilodrostat (LCI699), which was intended to reduce serum aldosterone levels and manage hypertension. It was soon discovered, nevertheless, that Osilodrostat also inhibits 11-beta hydroxylase (CYP11B1), which lowers serum cortisol levels.…”
mentioning
confidence: 99%
“… 8 , 10 Differences in diastolic blood pressure, the secondary objective, were achieved at the 2 mg dose. 6 Baxdrostat was shown to reach its maximal plasma level in 4 h, causing a dose‐dependent drop in serum aldosterone without changing cortisol levels as one of the exploratory endpoints. 8 , 10 The background medication utilized in the experiment was the same for all groups.…”
mentioning
confidence: 99%